2019
DOI: 10.14309/ctg.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Allergen-Specific Immune Signature-Directed Approach to Dietary Elimination in Eosinophilic Esophagitis

Abstract: OBJECTIVES: Dietary elimination for treatment of eosinophilic esophagitis (EoE) is limited by lack of accuracy in current allergy tests. We aimed to develop an immunologic approach to identify dietary triggers and prospectively test allergen-specific immune signature-guided dietary elimination therapy. METHODS: In the first phase, we developed and assessed 2 methods for determining selected food triggers using samples from 24 adults with EoE: a CD4+ T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…A recent study combined peripheral CD4+ T‐cell proliferation in combination with oesophageal tissue Immunoglobulin G4 food‐specific detection to direct food elimination. The results led to improvement in patients but few with resolution 39 …”
Section: Discussionmentioning
confidence: 94%
“…A recent study combined peripheral CD4+ T‐cell proliferation in combination with oesophageal tissue Immunoglobulin G4 food‐specific detection to direct food elimination. The results led to improvement in patients but few with resolution 39 …”
Section: Discussionmentioning
confidence: 94%
“…Eosinophilic esophagitis or gastroenteritis has also been related to FA, and dietary restriction is a common therapeutic approach in these disorders. 34,35 Other biomarkers such as total IgE 36 or FeNO 37,38 can also be modified or influenced by FA.…”
Section: Discussionmentioning
confidence: 99%
“…Events were gated by Lymphocytes, Live/Dead negative, CD8 − , CD19 − , CD3 + , CD4 + , CD45RA − , CD45RO + (Figure S2). As food-specific IgG4 levels have been shown to correlate with clinical EoE food allergy, 7,[19][20][21][22] we first examined total and milkspecific IgG4 levels in the plasma of control or clinical EoE milk allergy subjects. We did not observe a significant difference in total IgG4 levels (Figure 1A), but did observe a non-significant increase in milk-specific IgG4 levels in clinical EoE milk allergy subjects compared with controls (Figure 1B).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…While prior studies in animal models and human subjects have shown that allergen-specific T H cells circulate in the blood of patients with EoE, 7,12,14,17 examinations of memory T H -cell populations have not been undertaken. We therefore sought to determine whether We next sought to quantify the extent to which milk-dependent memory T H -cell proliferation associated with clinical EoE milk allergy.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%